2011
DOI: 10.1152/physiol.00046.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation and Physiology of Mitochondrial Proton Leak

Abstract: Mitochondria couple respiration to ATP synthesis through an electrochemical proton gradient. Proton leak across the inner membrane allows adjustment of the coupling efficiency. The aim of this review is threefold: 1) introduce the unfamiliar reader to proton leak and its physiological significance, 2) review the role and regulation of uncoupling proteins, and 3) outline the prospects of proton leak as an avenue to treat obesity, diabetes, and age-related disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
332
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(365 citation statements)
references
References 231 publications
12
332
1
3
Order By: Relevance
“…However, not all of the energy available in the electrochemical gradient is coupled to ATP synthesis. Some of the energy is consumed by proton leak reactions, by which protons pumped out of the matrix are able to reflow back along the proton gradient through proton conductance pathways in the inner membrane that bypass the ATP synthase (11,12). As a result, the energy derived from the metabolic oxidation reaction is dissipated as heat.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…However, not all of the energy available in the electrochemical gradient is coupled to ATP synthesis. Some of the energy is consumed by proton leak reactions, by which protons pumped out of the matrix are able to reflow back along the proton gradient through proton conductance pathways in the inner membrane that bypass the ATP synthase (11,12). As a result, the energy derived from the metabolic oxidation reaction is dissipated as heat.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…It is possible that CZ5 uncouples OXPHOS via its chemical properties, namely lipophilicity and weak acidity. Additionally CZ5 may also interact with certain proteins that mediate proton leak and are expressed specifically in myocytes and adipocytes [15]. However, neither GDP nor carboxyatractyloside was able to attenuate the uncoupling effects of CZ5 (data not shown), suggesting no involvement of UCPs or the adenine nucleotide translocase in these effects.…”
Section: Discussionmentioning
confidence: 91%
“…Experiments using transgenic mice overexpressing uncoupling proteins (UCPs) in metabolic tissues showed that locally uncoupling oxidative phosphorylation (OXPHOS) could combat obesity and improve glucose homeostasis to varying extents [12][13][14]. Yet it remains to be verified how these UCPs are regulated by physiological ligands [15]. Pharmacological evidence for the effectiveness of uncoupling includes the potent anti-obesity effect observed with 2,4-dinitrophenol (DNP), a chemical uncoupler with a non-specific effect widely used in the 1930s [16].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of superoxide. 38,[40][41][42] and other redox-active species (e.g. 4-HNE 43,44 ) in modulating UCP1 function is the subject of debate.…”
Section: Adsod2 Deletion Increases Uncoupled Respiration In Cells Andmentioning
confidence: 99%